Programación teatral antes, durante y después de la pandemia: dos casos desde el Gran Teatro Nacional - Salas Torreblanca, Mauricio Manuel (2022)
This work of professional sufficiency presents two experiences developed during my management as General Coordinator and Programmer of the Gran Teatro Nacional, in the period 2017-2021, pre, during and post pandemic. Both experiences, the outdoor festival Afuera Fest and the audiovisual platform GTN live, premiered in February 2018 and March 2020 respectively, endure until today and constitute an important legacy for the institution and for its purposes towards the citizenry: promotion of citizen participation in culture and diversification of the cultural offer. They are also evidence of my professional development as a communicator and cultural manager in the public sphere over the last 25 years.